KOMUNIKASI INTERPERSONAL PENDAMPING PROGRAM KELUARGA HARAPAN (PKH) KEPADA KELUARGA PENERIMA MANFAAT (KPM) (Studi pada PKH di Kabupaten Padang Pariaman) - Eka Ona Sutera; Asmawi Asmawi; Sarmiati Sarmiati (Universitas Islam Negeri Imam Bonjol Padang, 2020)
This research is motivated by the presence of PKH Partners as the spearhead of the government in changing the behavior of poor families thus they can get out of poverty. This study aims to determine the interpersonal communication carried out by PKH Partners to KPM and obstacles in implementing of interpersonal communication. The theory used was the Source Credibility Theory proposed by Hovland, Janis and Kelley. The approach of this research is descriptive qualitative.The results showed that interpersonal communication carried out by PKH Partners were applied in activities of compulsory P2K2 meeting, home visits and visits to relevant agencies by using face to face dialogue through verbal and non verbal communication. Verbal communication is done verbally by PKH Partners as a communicator to KPM as the communicant through discussion and question and answer, and non-verbal communication in the form of a touch specifically made for the disabled and elderly. The nature of the relationship between PKH Partners and KPM is interdependence because each party has the obligation to accompany and be accompanied, if not the aid fund is deferred. PKH Partners and KPM communicate actively at each meeting until all the required information has been obtained and KPM has interpreted all the messages conveyed. The message conveyed in connection with improving the quality of life of KPM families and PKH Partners did not use the media because communication was done face-to-face. To create effective communication The PKH Partners an openness attitude, motivation, sympathy and empathy as well as equality, and the attitude that shown by PKH Partners creates a sense of confidence of KPM thus the message delivered by PKH Partners received and implemented well by KPM. Meanwhile the barriers of interpersonal communication that done by PKH Partners were, limited knowledge, generation differences and physical limitations